2020
DOI: 10.1111/cogs.12837
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Strategies for Gathering Evidence About Biological Kinds

Abstract: How do people gather samples of evidence to learn about the world? Adults often prefer to sample evidence from diverse sources-for example, choosing to test a robin and a turkey to find out if something is true of birds in general. Children below age 9, however, often do not consider sample diversity, instead treating non-diverse samples (e.g., two robins) and diverse samples as equivalently informative. The current study (N = 247) found that this discontinuity stems from developmental changes in standards for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…These models consistently suggested that top‐down processes impact FN400, indexing familiarity perception, which results from a discrepancy among task‐related previous expectations and stimuli‐related processing, with greater FN400 amplitudes for increased processing discrepancies (Leynes & Mok, 2020; Mecklinger & Bader, 2020). Diverse premises meet smaller processing discrepancies than non‐diverse premises because diverse premises support CBI more than non‐diverse premises (Feeney & Heit, 2011; Foster‐Hanson et al ., 2020; Heit et al ., 2005; Kalkstein et al ., 2020). Therefore, the diverse premises elicit more positive FN400 amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These models consistently suggested that top‐down processes impact FN400, indexing familiarity perception, which results from a discrepancy among task‐related previous expectations and stimuli‐related processing, with greater FN400 amplitudes for increased processing discrepancies (Leynes & Mok, 2020; Mecklinger & Bader, 2020). Diverse premises meet smaller processing discrepancies than non‐diverse premises because diverse premises support CBI more than non‐diverse premises (Feeney & Heit, 2011; Foster‐Hanson et al ., 2020; Heit et al ., 2005; Kalkstein et al ., 2020). Therefore, the diverse premises elicit more positive FN400 amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in children and older adults remains unclear. Some studies have found that children may ignore diverse evidence, focusing on the degree of typicality (Foster‐Hanson et al ., 2020; Lawson, 2019; Rhodes & Liebenson, 2015). Future research should explore the development of the influence of premise typicality on the diversity effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations